Expanding global military capacity for humanitarian intervention - O'Hanlon, Michael E. (Brookings Institution Press, 2003)
"Humanitarian military intervention and muscular peace operations have been partially effective in recent years in saving thousands of lives from the Balkans to Haiti to Somalia to Cambodia to Mozambique. However, success has often been mitigated by the international community's unwillingness or inability to quickly send enough forces capable of dealing with a situation decisively. In other cases, the international community has essentially stood aside as massive but possibly preventable humanitarian tragedies have taken place - for instance, in Angola and Rwanda in the mid-1990s and in Congo as this book goes to press. Sometimes these failures have simply been the result of an insufficient pool of available military and police forces to conduct the needed intervention or stabilization missions."